Effect of home-based early intensive behavioral intervention using VB-MAPP on verbal ability in children with autism spectrum disorder - Chen Xueping; Zhang Qingying; Wu Yi; Wang Hongwu; Rao Wenwang; Li Duo; Ou Yan; Su Shaoyuan; Liu Guimin (Sichuan jingshen weisheng, 2023)
BackgroundHome-based intervention occupies a prominent place in the treatment of autism spectrum disorder （ASD） in children， whereas previous studies on the effect of home-based early intensive behavioral intervention on verbal ability of children with ASD are somewhat inadequate.ObjectiveTo study the effects of intensive family behavioral of intervention based on Verbal Behavior Milestones Assessment and Placement Program （VB-MAPP） on the language ability of children with ASD， so as to provide references for the development of family intervention strategies for children with ASD.MethodsChildren aged 2 to 3 years old who attended the Children's Rehabilitation Department of the Second Affiliated Hospital of Shantou University Medical College from September 2020 to December 2021 and met the Diagnostic and Statistical Manual of Mental Disorders， fifth edition （DSM-5） diagnostic criteria for ASD were selected as the study objects. A non-randomized concurrent control trial was conducted to compare a study group （n=24） receiving home-based early intensive behavioral intervention using VB-MAPP with a control group （n=14） receiving training from other special institutions or early childhood education institutions. The intervention lasted for 6 months in both groups. Before and after the intervention， the VB-MAPP milestone assessment was performed in the two groups， and the VB-MAPP milestone score， mand， trac and listener responds were selected as the study indicators. Then the intervention effect was compared between two groups， and the multiple linear regression was performed to screen the related influencing factors.ResultsAfter intervention， the total milestone assessment score， mand， tact and listener responds scores of study group were higher than those of control group， with statistical difference （Z=-4.339~-2.195， P<0.05 or 0.01）. Multiple linear regression analysis denoted that the average weekly hours of home-based intervention in the first three months had certain effect on listener responds （β=1.029， P<0.05）.ConclusionApplication of home-based early intensive behavior intervention using VB-MAPP may contribute to the improvement of verbal abilities such as mand， tact and listener responds in children with ASD. ［Funded by 2020 Guangdong Provincial Science and Technology Innovation Strategy Special Fund （number， 20200601）］